PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN TULUNGAGUNG - Dewi Cahyaningtyas (Universitas Islam Kadiri, 2019)
This research used explanative survey method by spreading quetionaire to collect data. Sample in this research is the overall employees in the General Section of Local Government Secretariat Tulungagung Regency about 100 people who are the population in this research taken by Non probability sampling technic. Instrument used in this research is quetionaire that had been through validity and reability tests by Pearson’s Product Moment Correlation and Cronbach’s Alpha. Based on the analysis results of research, known that leadership style has a significant influence in the amount of democratic style of 7,6 %, bureaucratic style of 4,6 %, freedom style of 5,4 % and otocratic style of 4,2 %. While motivation partially has significant influence to performance are physic needed and safety needed in the amount of 5,4 %, social needed in the amount of 0,01 %, and egoistic needed in the amount of 6,3 %. Together, the influence of leadhership style and motivation to employee’s performance on General Section of Local Government Secretariat Tulungagung Regency as big as 29,3 %. The results of these research shows that the influence of leadership style and motivation performance against employees in the General Section of Local Government Secretariat Tulungagung Regency. In order to that, is suggested that the head of General Section as leader could motivate employees with complete office facilities and apply the appropriate leadership style factual circumstances.